Дослідження Амвросіївської стоянки в 2009 р. - Кротова, О.О.; Сніжко, І.А.; Грибченко, Ю.М. (Археологічні дослідження в Україні, 2010)
The authors present the preliminary results of 2009 investigations of Amvrosijivka Upper Paleolithic base camp. The information about peculiarity of Pleistocene sediments on the territory of the site and continues of excavations of western part of the settlement are given.